Podkomorzy kaliski Mikołaj z Wolicy. Herb Doliwów z Kępy, Wolicy i Rozdrażewa = Kalisz county chamberlain Mikołaj from Wolica. The coat of arms of Doliwas from Kępa, Wolica, and Rozdrażew - Benyskiewicz, Krzysztof (1959- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is dedicated to the Kalisz chamberlain Mikołaj from Wolica, a fourteenth-century representative of the Doliwa family. It consists of two parts. The first registers the achievements of historiography on the matter of origins and family ties and presents new proposals concerning the clerical and political career of the Great Poland magnate.
Keywords: Mikołaj z Wolicy; Urzędnicy - Polska; 14 w.